Conflicting commitments the politics of enforcing immigrant worker rights in San Jose and Houston - Gleeson, Shannon, 1980- (ILR Press, 2012)
"In Conflicting Commitments, Shannon Gleeson goes beyond the debate over federal immigration policy to examine the complicated terrain of immigrant worker rights. Federal law requires that basic labor standards apply to all workers, yet this principle clashes with increasingly restrictive immigration laws and creates a confusing bureaucratic terrain for local policymakers and labor advocates. Gleeson examines this issue in two of the largest immigrant gateways in the country: San Jose, California, and Houston, Texas. Conflicting Commitments reveals two cities with very different approaches to addressing the exploitation of immigrant workers--both involving the strategic coordination of a range of bureaucratic brokers, but in strikingly different ways. Drawing on the real life accounts of ordinary workers, federal, state, and local government officials, community organizers, and consular staff, Gleeson argues that local political contexts matter for protecting undocumented workers in particular. Providing a rich description of the bureaucratic minefields of labor law, and the explosive politics of immigrant rights, Gleeson shows how the lessons learned from San Jose and Houston can inform models for upholding labor and human rights in the United States"--Publisher's Web site.